The Development of Auditory Proficiency in French and English as Foreign Languages in Secondary Schools in Flanders - Housen, Alex; Janssens, Sonja; Pierrard, Michel (Círculo de Lingüística Aplicada a la Comunicación, 2023)
A group of 125 Dutch-speaking students from five different secondary schools in Flanders, Belgium, were tested for oral production and listening comprehension proficiency in both English and French as part of a pilot study intended to examine outcomes and causal factors in the simultaneous learning of two foreign languages in an educational context. While overall the results indicate higher levels of proficiency in English than in French, pointing to the dominance of extra-curricular factors (sociocultural context) over curricular factors (amount of formal instruction and classroom contact), a breakdown of the scores on the various test components suggests a more intricate interplay between both types of factors as determinants of oral language proficiency in a foreign language environment.